Analisis Faktor-faktor yang Mempengaruhi Kejadian Stunting pada Balita - Iin Setiawati; Dana Daniati; Selvia Nurul Qomari (Universitas Faletehan, 2025)
Many toddlers in Indonesia still suffered from chronic malnutrition. The condition was still not in line with sustainable development goals (SDGs)'s target of eliminating all forms of malnutrition by 2030. This study aimed to analyse the influence of maternal anemia, low birth weight (LBW), and birth spacing on incidence of stunting. The study employed an analytical approach with a cross-sectional design. The research instrument was a checklist sheet with secondary data sources from monitoring the local area of maternal and child health (PWS KIA) and registers. A total of 93 toddlers were selected for this study using simple random sampling. The statistical tests used were chi-square tests. The results showed that almost all of toddlers did not have a history of anemia (79.57%). Similarly, nearly all toddlers did not have a history of low birth weight (LBW) (94.62%). Almost half of toddlers had an interpregnancy interval of two years (49.46%). Most toddlers were not affected by stunting (67.74%). The data analysis showed that a history of anemia did not affect on stunting (ρ = 0.632 and OR= 1.29). However, history of LBW did influence stunting (ρ = 0.001 and OR = 119.23). The interval between pregnancies also affected on stunting (ρ = 0.000 and OR = 25.75). Through the provision of good nutrition and proper parenting, the risk of stunting in toddlers can be reduced. History of anemia had no effect, while history of LBW and interpregnancy interval had an effect on the incidence of stunting. The next pregnancy needs to be planned by setting a minimum spacing of 2 years to 5 years.